2016
DOI: 10.1002/jcp.25494
|View full text |Cite
|
Sign up to set email alerts
|

Coumestrol Inhibits Proliferation and Migration of Prostate Cancer Cells by Regulating AKT, ERK1/2, and JNK MAPK Cell Signaling Cascades

Abstract: Coumestrol is the one of the major phytoestrogens which is abundant in soybeans, legumes, brussel sprouts, and spinach. The beneficial effects of coumestrol are well known in various biological processes including; neuroprotective effects on the nervous system, function of the female reproductive system, anti-bacterial properties, and anti-cancer effects. Although the anti-tumor activity of coumestrol has been demonstrated for ovarian, breast, lung, and cervical cancers, little is known of its effects on prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…The Akt signaling pathway principally regulates the activity of cancer cells (30,31). Previous studies have indicated that the Akt signaling pathway is a key factor in the viability and migration of a number of types of tumor including colorectal (32), and prostate cancer (33), and glioblastoma (34) and osteosarcoma (35). Additionally, the Akt signaling pathway is an important regulator of breast cancer (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The Akt signaling pathway principally regulates the activity of cancer cells (30,31). Previous studies have indicated that the Akt signaling pathway is a key factor in the viability and migration of a number of types of tumor including colorectal (32), and prostate cancer (33), and glioblastoma (34) and osteosarcoma (35). Additionally, the Akt signaling pathway is an important regulator of breast cancer (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…These agents include natural compounds derived from plants, vegetables, and fruits that are widely used due to minimum of side effects compared to traditional medicines and as an alternative strategy for treatment of cancers resistance to classical therapeutic agents (Grayson, ). We reported previously that coumestrol, a phytoestrogen found in soy products, suppresses phosphorylation of AKT in a dose‐ and time‐dependent manner (Lim, Jeong, Bazer, & Song, ). In addition, inhibition of the PI3K/AKT pathway using a pharmacological inhibitor, LY294002, enhanced inhibition of proliferation of PC‐3 and LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Coumestrol is a polyphenol with oestrogen properties found in raw clover sprouts, red clover, alfaalfa, soybeans, legumes, Brussel sprouts and spinach. This bioactive compound might elicit anticancer effects by affecting viability and mitochondrial functions and provoking apoptosis by inhibition of PI3K/AKT and activation of MAPKs (ERK1/2 and JNK) . Interestingly, coumestrol has been shown to activate SIRT‐1 and thereby initiating MB in cultured mouse skeletal muscle cells .…”
Section: Nutritional Strategies Targeting Mitochondrial Dysfunction Imentioning
confidence: 99%
“…This bioactive compound might elicit anticancer effects by affecting viability and mitochondrial functions and provoking apoptosis by inhibition of PI3K/AKT and activation of MAPKs (ERK1/ 2 and JNK). 80 Interestingly, coumestrol has been shown to activate SIRT-1 and thereby initiating MB in cultured mouse skeletal muscle cells. 81 Using human placental choriocarcinoma cells, it was recently shown that coumestrol induces apoptotic effects on these cells by regulating cell signalling and mitochondrial-mediated functions mainly by stimulating ROS production.…”
Section: Targeting Mitochondrial Dysfunction In Ckdmentioning
confidence: 99%